A direct role for ATP1A1 in unconventional secretion of fibroblast growth factor 2 - Zacherl, Sonja; La Venuta, Giuseppe; Müller, Hans-Michael; Wegehingel, Sabine; Dimou, Eleni; Sehr, Peter; Lewis, Joe D.; Erfle, Holger; Pepperkok, Rainer; Nickel, Walter (The journal of biological chemistry, 2015)
Previous studies proposed a role for the Na/K-ATPase in unconventional secretion of fibroblast growth factor 2 (FGF2). This conclusion was based upon pharmacological inhibition of FGF2 secretion in the presence of ouabain. However, neither independent experimental evidence nor a potential mechanism was provided. Based upon an unbiased RNAi screen, we now report the identification of ATP1A1, the α1-chain of the Na/K-ATPase, as a factor required for efficient secretion of FGF2. As opposed to ATP1A1, down-regulation of the β1- and β3-chains (ATP1B1 and ATP1B3) of the Na/K-ATPase did not affect FGF2 secretion, suggesting that they are dispensable for this process. These findings indicate that it is not the membrane potential-generating function of the Na/K-ATPase complex but rather a so far unidentified role of potentially unassembled α1-chains that is critical for unconventional secretion of FGF2. Consistently, in the absence of β-chains, we found a direct interaction between the cytoplasmic domain of ATP1A1 and FGF2 with submicromolar affinity. Based upon these observations, we propose that ATP1A1 is a recruitment factor for FGF2 at the inner leaflet of plasma membranes that may control phosphatidylinositol 4,5-bisphosphate-dependent membrane translocation as part of the unconventional secretory pathway of FGF2.